Implications of COVID-19 on the teaching and learning of undergraduate medical imaging students - Sayed, Inayatullah Shah; Zamri, Muhammad Haidir (Cureus, Inc, 2022)
To preserve public health and prevent the spread of COVID-19, academic institutions curtailed face-to-face instruction and learning after the outbreak. The traditional techniques for education were modified, and new ways of instructing students were implemented. It presented a number of difficulties for the educational system, particularly for universities offering healthcare education. Therefore, the aim of this research was to look into how COVID-19 affected the teaching and learning of undergraduate medical imaging students. The ScienceDirect, Oxford University Press Journals, Cambridge University Press Journals, and Taylor & Francis Online databases were searched, and a total of 14 papers met the inclusion and exclusion criteria and were selected for further analysis. The literature was analyzed using a thematic approach, with recurring themes brought to light. The effects of COVID-19 on medical imaging education include but are not limited to the more rapid adoption of online education and new approaches to assessing and guiding students. Online teaching for medical imaging students influenced their learning environment, interaction, and motivation. The new COVID-19 safety requirements and procedures in hospitals have profoundly impacted clinical practice. Additionally, students’ research activities were also affected. We anticipate that the findings of this study will enable us to be better equipped to assist students in comparable circumstances in the future.